Toward 10 000‐fold sensitivity improvement of oligosaccharides in capillary electrophoresis using large‐volume sample stacking with an electroosmotic flow pump combined with field‐amplified sample injection. Issue 16 (12th July 2013) - Kawai, Takayuki; Ueda, Masumi; Fukushima, Yudai; Sueyoshi, Kenji; Kitagawa, Fumihiko; Otsuka, Koji; Guttman, Andras
<x xml:space="preserve">Abstract</x> A combination of two online sample concentration techniques, large‐volume sample stacking with an electroosmotic flow pump (LVSEP) and field‐amplified sample injection (FASI), was investigated in CE to achieve highly sensitive oligosaccharide analysis. In CE with LVSEP‐FASI, analytes injected throughout the capillary were concentrated on the basis of LVSEP, followed by an electrokinetic introduction of concentrated analytes from the inlet vial by the FASI mechanism. After switching the inlet vial solution from the sample to running buffer, the concentrated analytes were then separated by CZE. In the present LVSEP‐FASI‐CZE, pressure was applied to the capillary inlet until the inlet vial solution was exchanged. The applied pressure generated a counterflow against the EOF. It kept the stacked sample zone within the capillary, minimizing loss of concentrated analytes. Fluorescein was first analyzed by LVSEP‐FASI‐CZE to optimize preconcentration condition. Up to 110 000‐fold sensitivity increase was obtained with 200 μL of sample, compared to normal CZE with sample injection of 0.3 psi for 3 s (ca. 1.7 nL). From the results, the pressure application improved the efficiency of the FASI‐mode concentration significantly at total concentration time longer than 10 min. In the analysis of maltoheptaose, a 10 000‐fold sensitivity increase was achieved, which is the highest concentration efficiency ever reported in CE of oligosaccharides. The relative standard deviations of the detection time and peak height were 2.4 and 11%, respectively. In the analysis of glucose oligomer, up to 8600‐fold sensitivity increases were achieved without reducing the separation performance of conventional CZE.